Death and the superhero in the philosophical thought of Bogusław Miciński - Kasperska-Ścibior , Małgorzata (Hybris, 2013)
The purpose of this short essay is to present the profile of pre-war polish writer and philosopher Bolesław Miciński. On the occasion of the second edition of his writings it is worth to recall the memory of him. This exceptional penman suffered from his youth and awareness of impending death permeated his thought and creativity. Short life and war caused the forgetting of his achievements and literary output. This is a huge loss because his work was ahead of his time. Popular literature has a special place in his work. Miciński believed that literary texts looking for the truth about human life. For his master Jerzy Stempowski thought that literature has the value of describing and explaining the truth about the meaning of the existence of man. The main characters of his philosophizing essays were superheroes and death. Philosopher did not accept the existing system of values, but sought their real meaning.These experiences have brought him close to the existentialists.